Desenvolvimento de um conjunto de modelagem de alta resolução para os métodos eletromagnéticos indutivos - MELO, Alberto Leandro de (Universidade Federal do Pará, 2014)
Electromagnetic analog modelling has been a powerful tool to study the electromagnetic response of a great varieties of survey techniques of different geological models. In the applications of The electromagnetic methods in the investigations of subsurface contaminations of in great demand recently, very low anomalies (of the order of 0.01% Hp) are obtained. To study in the laboratory the problems of the electromagnetic surveys of low induction number targets, an electromagnet reduced scale model set-up is designed and construed. This set-up operates in the frequency range off 1 kHz to 1 MHz. The developed transmitting system generate a high magnetic flux density by passing a 3 AP-P current in it. The receiving system, consist of a set coils and amplifier coupled in it, has a sensibility of 3 V/A/m at 10 kHz with gradient of 20 dB/dec frequency. The overall resolution of the set-up is 0.025% HP, obtained due to the high sensitivity of the received system to generate primary field. The set-up also has a very precise mechanical system that permits locate the coils at any arbitrary position with a resolution of 1 mm and a precision 0.5 mm. The Tx-Rx system cam be moved linearly with great precision up to 1715 mm in length, by rotating a spindle employing a microprocessor controlled stepper motor attached to it. With set-up, it is possible to simulate a great variety of electromagnetic survey techniques of Slingram systems, that is dipole-dipole configurations. Besides good mechanical and electromagnetic measurements resolutions; all the process of data acquisition and other operations in the set-up cam be controlled through a computer.